Impacts Socioéconomiques Et Sanitaires De L’exploitation Agricole De La Plaine Inondable Todé- Gbamè Au Bénin - Atidegla, Séraphin Capo; Degbo, Hermine Elisée; Azonhe, Thierry; Agbossou, Euloge Kossi (European Scientific Journal, ESJ, 2017)
The present study aims to determinate the prevalence of the diseases linked to the agricultural exploitation of Todé-Gbamè plain liable to flooding in Benin and to assess the related work wasting times. To reach the study’s objectives, sanitary, economic and social investigations were conducted with the farmers and health workers of the Commune of Adjohoun. Inquiry was also based on agronomic trial regarding maize yield in the plateau and the plain liable to flooding. The study revealed that soils fertility and farmers income are higher in the plain than that of the plateau. Moreover, the annual prevalence of diseases are globally high in the plain liable to flooding, followed by both plain and plateau and finally by the plateau with the paludism at the top and present at 100% in the three areas. Then, we have respiratory infections, gastroenteritis and dermatosis with a remarkable presence in the plain and both plain and plateau. Finally, the dermatosis was not recorded in the plateau. Consequently, the annual loss working days due to diseases were globally high in the plain liable to flooding, followed by both plain and plateau. With regards to this critical situation, the main identified causes are cropping practices and less advisable farmers’ behaviors in Todé-gbamè’s plain liable to flooding. That is why; it is urging to enhance the technical capacities of the farmers of the study area through a subsequent training